Case report: A novel heterozygous frameshift mutation of ACAN in a Chinese family with short stature and advanced bone age - Huang, Hao; Jin, Jieyuan; Xiang, Rong; Wang, Xia (Frontiers in Genetics, 2023)
Short stature (OMIM: 165800) is a common pediatric disorder. Any abnormality in the cartilage formation of the growth plate can cause short stature. Aggrecan, encoded by ACAN, is an important component of the extracellular matrix. Mutations in ACAN have been reported to cause short stature. In the present study, we enrolled a Chinese family with short stature and advanced bone age across three generations. Whole-exome sequencing (WES) was performed on the proband to detect the candidate genes causing short stature in the family. A novel heterozygous frameshift mutation (NM_013227.3:c.7230delT; NP_001356197.1: p.Phe2410Leufs*9) of the ACAN gene was confirmed to be a genetic lesion in this family. This variant, which was located in a functional site globular 3 (G3) domain of ACAN and predicted to be deleterious by informatics programs, was co-segregated with the affected family members by performing Sanger sequencing. Literatures review of growth hormone (GH) treatment outcome of all previously reported ACAN patients suggesting that the G3 domain of ACAN may be critical in the development of short stature and GH treatment. These findings not only contribute to the genetic diagnosis and counseling of the family, but will also expand the mutation spectrum of ACAN.